1982
DOI: 10.1007/bf00039217
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility and incompatibility in witloof-chicory (Cichorium intybus L.). 3. Gametic competition after mixed pollinations and double pollinations

A. H. Eenink

Abstract: In witloof-chicory research was carried out on the occurrence of gametic competition after mixed or double pollinations with self-and foreign pollen. In part of the experiments flower heads were emasculated before pollination. Gametic competition was deduced from the percentages of hybrid seeds in the various experiments with flower colour functioning as a marker.Among self pollen parent (SPP) clones large differences occurred for frequency of germinated pollen grains after self pollination. These differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 15 publications
(9 reference statements)
0
14
0
Order By: Relevance
“…Results of sequential pollination studies on other species are varied. In a similar artificial pollination study on witloof chicory (Cichorium intybus), Eenink (1982) found that second pollinations delayed 60 minutes or more were ineffective.…”
Section: Effects Of Sequential Pollination On Mating Systemmentioning
confidence: 96%
“…Results of sequential pollination studies on other species are varied. In a similar artificial pollination study on witloof chicory (Cichorium intybus), Eenink (1982) found that second pollinations delayed 60 minutes or more were ineffective.…”
Section: Effects Of Sequential Pollination On Mating Systemmentioning
confidence: 96%
“…This may be ascribed to the above speculation . Another contribution to this enhanced self-seed formation is possibly made by a specific parental combination effect (SPP 560 x FPP 1045) which was observed earlier in Cichorium (EENINK, 1982) . Such parental effects resulting in gamete selection, have been found in various genera such as Allium (CURRAH, 1981) and Nemesia (ROBACKER & ASCHER, 1981) with styles capable to discriminate among pollen tubes from different pollinators .…”
Section: Resultsmentioning
confidence: 99%
“…SPP flower heads were not emasculated to approach as much as possible the natural and practical situation . Besides, emasculation may disturb the balance between male and female parts of the flower head (LINSKENS, 1964), influencing the frequency of self-seed formation (EENINK, 1982) .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations